ONLINE SERVICES FOR 'OPEN' COOPERATION OF UNIVERSITY TEACHERS - Manzhula, А.М.; Popko, Т.С. (Journal of Information Technologies in Education (ITE), 2014)
In this article the basic stages of creating open educational resources were defined (creation,storing, protection, publication, social assessment, search of creative partners, forming a culture of social exchange and collaboration), as well as analysis of tools for such type of creative activity was made, following free online service were described: Google docs, Google Drive, Yandex Disc,Creative Commons, Innovative Teachers Net. The intensity of ICT and open educational resources use, general attitude and position toward open educational resources among teachers were analyzed.